Case report: A familial B-acute lymphoblastic leukemia associated with a new germline pathogenic variant in PAX5. The first report in Mexico - García-Solorio, Joaquín; Martínez-Villegas, Octavio; Rodríguez-Corona, Ulises; Molina-Garay, Carolina; Jiménez-Olivares, Marco; Carrillo-Sanchez, Karol; Mendoza-Caamal, Elvia C.; Muñoz-Rivas, Anallely; Villegas-Torres, Beatriz E.; Cervera, Alejandra; Flores-Lagunes, Luis L.; Alaez-Verson, Carmen (Frontiers in Oncology, 2024)
B-cell acute lymphoblastic leukemia (B-ALL) is one of the most common childhood cancers worldwide. Although most cases are sporadic, some familial forms, inherited as autosomal dominant traits with incomplete penetrance, have been described over the last few years. Germline pathogenic variants in transcription factors such as PAX5, IKZF1, and ETV6 have been identified as causal in familial forms. The proband was a 7-year-old Mexican girl diagnosed with high-risk B-ALL at five years and 11 months of age. Family history showed that the proband’s mother had high-risk B-ALL at 16 months of age. She received chemotherapy and was discharged at nine years of age without any evidence of recurrence of leukemia. The proband’s father was outside the family nucleus, but no history of leukemia or cancer was present up to the last contact with the mother. We performed exome sequencing on the proband and the proband’s mother and identified the PAX5 variant NM_016734.3:c.963del: p.(Ala322LeufsTer11), located in the transactivation domain of the PAX5 protein. The variant was classified as probably pathogenic according to the ACMG criteria. To the best of our knowledge, this is the first Mexican family with an inherited increased risk of childhood B-ALL caused by a novel germline pathogenic variant of PAX5. Identifying individuals with a hereditary predisposition to cancer is essential for modern oncological practice. Individuals at high risk of leukemia would benefit from hematopoietic stem cell transplantation, but family members carrying the pathogenic variant should be excluded as hematopoietic stem cell donors.